Effect of the CCL5-Releasing Fibrin Gel for Intervertebral Disc Regeneration. (April 2020) - Zhou, Zhiyu; Zeiter, Stephan; Schmid, Tanja; Sakai, Daisuke; Iatridis, James C.; Zhou, Guangqian; Richards, R. Geoff; Alini, Mauro; Grad, Sibylle; Li, Zhen
Objective: To explore if chemokine (C-C motif) ligand 5 (CCL5) delivery could recruit annulus fibrosus (AF) cells to the injury sites and facilitate the repair of ruptured AF. Design: The effects of CCL5 on bovine AF cells in vitro were tested by transwell assay and quantitative real-time polymerase chain reaction. Fibrin gel containing CCL5 was used to treat annulotomized bovine caudal discs cultured under dynamic loading conditions. After 14 days of loading, the samples were collected for histological examination. A pilot animal study was performed using sheep cervical discs to investigate the effect of fibrin gel encapsulated with CCL5 for the treatment of ruptured AF. After 14 weeks, the animals were sacrificed, and the discs were scanned with magnetic resonance imaging before histopathological examination. Results: CCL5 showed a chemotactic effect on AF cells in a dose-dependent manner. AF cells cultured with CCL5 in vitro did not show any change of the gene expression of CCL5 receptors, catabolic and proinflammatory markers. In vitro release study showed that CCL5 exhibited sustained release from the fibrin gel into the culture media; however, in the organ culture study CCL5 did not stimulate homing of AF cells toward the defect sites. The pilot animal study did not show any repair effect of CCL5. Conclusions: CCL5 has a chemotactic effect on AF cells in vitro, but no ex vivo or in vivo regenerative effect when delivered within fibrin gel. Further study with a stronger chemotactic agent and/or an alternate biomaterial that is more conductive of cell migration is warranted.